DEVELOPING STUDENTS' READING ABILITY THROUGH INTERACTIVE READ-ALOUD :A Experimental Study at Junior High School in Klaten - Suharmoko, - (2009)
The present research entitled Developing Students' Reading Ability through Interactive Read Aloud is aimed to investigate: (1) whether interactive read aloud technique effective in improving students' reading ability, and (2) the students' response toward implementation interactive read aloud. This research used quasi experimental method. this research was conducted at junior high school in Klaten, this research involving 40 students of grade VII in control group and 40 students in experimental group. The control group was given a treatment with three phases technique while experimental group was given a treatment with interactive read aloud technique. The instruments used in this research were reading comprehension test given for both groups experimental and control groups and questionnaires given to experimental group. To answer first research problem, the data from reading test were analyzed using t test. The results shows there were significance difference between the mean of experimental group posttest score and control group score whereas mean of experimental group posttest higher than the mean control group posttest. It means that the use of interactive read aloud was effective improving students' reading ability. The second research problem was answered by the data from questionnaires. The data show that in general, students give positive responses toward implementation interactive read aloud.